FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI - LUSIYANA DELIKARTIKA; FERRY FERRY (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to obtain the empirical evidence about the influence of insider ownership, firm size, return on assets, earning per share, risk, liquidity, and leverage to dividend payout ratio. Population in this research is non finance company which listed in Indonesia Stock Exchange for 3 years from 2012 until 2014. The sample selected based on purposive sampling method, so that 109 non finance companies sample were obtained. The hypothesis were tested with multiple regression analysis. The result of this research shows that return on assets, earning per share, and risk influence dividend policy. Insider ownership, firm size, liquidity and leverage did not influence dividend policy.